2019
DOI: 10.17159/sajs.2019/5516
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential effects of nevirapine in South African surface water on fish growth: A chronic exposure of Oreochromis mossambicus

Abstract: Aquatic environments around the world have become mixtures of different types of pollutants, including pharmaceuticals. The presence of pharmaceuticals in aquatic environments has raised concerns regarding the possibility of unintended effects on aquatic animals. South Africa is currently the largest consumer of HIV antiretroviral drugs (ARVs) worldwide. Nevirapine (NVP), a first-line ARV, has been associated with serious liver toxicity in humans and has been repeatedly detected in South African surface water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The presence of antiretroviral drugs has been reported in surface waters (rivers and man-made lakes (also called dams)), as well as wastewater influents and effluents in Africa (Wood et al 2015;Ngumba et al 2016bNgumba et al , 2020Abafe et al 2018;Nibamureke et al 2019). Surface waters around the globe have scarcely been studied for the Accepted Article presence of antiretroviral drugs, however, ARVDs have been detected in rivers, lakes in South Africa, Kenya, Zambia, and other parts of the world (Aminot et al 2015;Funke et al 2016;K'oreje et al 2016;Wooding et al 2017, Mosekiemang et al 2019Madikizela et al 2020;Ngumba et al 2020).…”
Section: Concentrations Of Antiretroviral Drugs In African Surface Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of antiretroviral drugs has been reported in surface waters (rivers and man-made lakes (also called dams)), as well as wastewater influents and effluents in Africa (Wood et al 2015;Ngumba et al 2016bNgumba et al , 2020Abafe et al 2018;Nibamureke et al 2019). Surface waters around the globe have scarcely been studied for the Accepted Article presence of antiretroviral drugs, however, ARVDs have been detected in rivers, lakes in South Africa, Kenya, Zambia, and other parts of the world (Aminot et al 2015;Funke et al 2016;K'oreje et al 2016;Wooding et al 2017, Mosekiemang et al 2019Madikizela et al 2020;Ngumba et al 2020).…”
Section: Concentrations Of Antiretroviral Drugs In African Surface Watermentioning
confidence: 99%
“…Degradation products of nevirapine cause skin rash and liver toxicity and there are growing concerns regarding exposure of nontarget aquatic organisms such as fish to highly specialized compounds such as ARVDs (Kolpin et al 2002, Nibamureke et al 2019). Research has shown that a concentration (1480 ng L –1 ) of nevirapine detected in South African waters did not have significant detrimental effects on Oreochromis mossambicus (Mozambique tilapia fish) juvenile growth in terms of length and body mass initially, but a reduction in growth rate after 1 to 2 mo of exposure was observed (Nibamureke et al 2019).…”
Section: Potential Effects On Humans and Aquatic Speciesmentioning
confidence: 99%
“…About 4.9 million of the infected are already in the ARVDs program, thus may increase the volume of ARVDs received by water sources. Nevirapine, abacavir, and efavirenz are commonly used as first‐line treatments against HIV (Abafe et al, 2018; Nibamureke et al, 2019). As a result, these compounds were identified as compounds of interest.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the potential impact of ARVs such as nevirapine (NVP) in SA surface water was assessed on the growth of Mozambique tilapia. After a chronic exposure at the laboratory, it was found that NVP detected in SA waters, did not detrimentally affect the early juvenile growth of the tilapia fish being tested (Nibamureke et al,2019). However, further investigation is still needed to test NVP on all life stages of fish (such as zebrafish) to safeguard water systems.…”
Section: Studies That Investigate Water Quality / Contamination In So...mentioning
confidence: 99%